Flood monitoring and alert system - Kok, How Meng (2024)
to the growing frequency and severity of natural disasters, particularly flooding occurrences, the field of environmental monitoring and disaster management has made significant advancements in recent years. This project addresses the critical need for an effective and practical approach for monitoring flood incidents and disseminating alerts by developing a flood monitoring and alert system. One of the most catastrophic natural disasters is flooding, which causes fatalities and significant property damage. Despite the government’s efforts to decrease the effects of floods by implementing various structural and non-structural strategies, flood concerns in Malaysia caused by the monsoon and flash floods remain. Besides that, some of the existing systems have limited applicability to cover all areas prone to flooding due to limitations in monitoring infrastructure and Android OS versions. To overcome these challenges, this project aims to design and implement a mobile application for flood monitoring and alert systems to deliver fast and precise flood alerts. The project adopts agile methodology and utilises tools such as Flutter with Dart language, Google Maps, Google Cloud, APIs, and Firebase. This project also integrates data from various sources, including current water level data, rainfall data, weather forecasts, and weather warning data. The system will consist of four major modules: the monitoring module, the alerting module, the map module, and the flood management module. The flood monitoring and alert system is a significant advancement in the flood management process. It provides accurate and real-time information for users to monitor flood risk levels and status. Additionally, users can receive alerts about potential flood events and rising water levels via push notifications. It also provides a user-friendly interface for easy access to flood information using geospatial visualisation.